1965
DOI: 10.1029/jz070i004p00923
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial heat flow near Alberta, Virginia

Abstract: Temperatures were measured to a depth of 312 m in a hole cored in granite at 36ø52.15'N, 77ø54.15'W (elevation 116 m), near Alberta, Virginia. The temperature gradient in the lower half of the hole is uniformly 18øC/km. The cause of a variable gradient in the upper half of the hole is thought to be movement of groundwater within the hole. The average thermal conductivity determined from measurements on 0.64-cm-thick disks is 7.8 mcal/cm sec øC, but the average conductivity computed by summing the thermal resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…However, amplitudes of temperature oscillation at these gradients apparently are no greater than a few hundreths of a degree C, and in reports in which consideration is given to the convective transfer of heat (e.g., Diment and Robertson, 1963;and Diment et al, 1965), it is generally concluded that, in view of the larger uncertainties that enter into such estimates, convective instability has a negligible effect on the determination of the earth' s thermal gradient or rate of heat flow. On the other hand, my investigations have confirmed the findings of others that under some conditions, temperature gradients become very large, and temperature oscillations of several tenths of a degree may occur in some wells (Diment et al, 1965;Diment, 1967;and Gretner, 1967). Thermal disturbances of this magnitude would seriously impair the accuracy of temperature measurements required to estimate groundwater velocities, for example, in a method suggested by Stallman (1963).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, amplitudes of temperature oscillation at these gradients apparently are no greater than a few hundreths of a degree C, and in reports in which consideration is given to the convective transfer of heat (e.g., Diment and Robertson, 1963;and Diment et al, 1965), it is generally concluded that, in view of the larger uncertainties that enter into such estimates, convective instability has a negligible effect on the determination of the earth' s thermal gradient or rate of heat flow. On the other hand, my investigations have confirmed the findings of others that under some conditions, temperature gradients become very large, and temperature oscillations of several tenths of a degree may occur in some wells (Diment et al, 1965;Diment, 1967;and Gretner, 1967). Thermal disturbances of this magnitude would seriously impair the accuracy of temperature measurements required to estimate groundwater velocities, for example, in a method suggested by Stallman (1963).…”
Section: Introductionsupporting
confidence: 79%
“…The temperature gradient between X.6 and 9.3 m was 5.5X10-20C m, a value just on the unstable side of the calculated critical cur\' c for this well. The water column at and below 9.d m appeared to be completely stable and thermal gradients were positive upward.AsDiment (1967) also observed in his experiments, the temperature fluctuations did not seem to be periodic, but rather to reflect complex superposition of many small movements. The intervals between peaks of the major oscillations showed only small correlation, if any, with the observed thermal gradients although the amplitudes of the fluctuations could be' related fairly well to the-%J&x FIG.…”
mentioning
confidence: 71%